2000
DOI: 10.15448/1980-864x.2000.1.24800
|View full text |Cite
|
Sign up to set email alerts
|

Religião e identificação étnica

Abstract: Este texto analisa os contatos inter-religiosos entre católicos e luteranos em Curitiba entre 1850-1919, a partir dos rituais de batismo, casamento e sepultamento.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…2. The Ranzi et al [5] mechanism gives very close agreement in magnitude with data (especially at φ=0.5), and is able to capture the roll-off and τ ign variation with φ as seen in data. The Ranzi et al [5] model slightly overpredicts the ignition delay times at φ=1 (above 980 K).…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…2. The Ranzi et al [5] mechanism gives very close agreement in magnitude with data (especially at φ=0.5), and is able to capture the roll-off and τ ign variation with φ as seen in data. The Ranzi et al [5] model slightly overpredicts the ignition delay times at φ=1 (above 980 K).…”
Section: Resultssupporting
confidence: 61%
“…n-dodecane/air τign results. τign predictions of the Ranzi et al [5] and the Zhang et al [6] mechanisms are also shown.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations